Positron emission tomography as a surrogate marker for evaluation of treatment response in patients with desmoid tumors under therapy with imatinib - Kasper, Bernd; Dimitrakopoulou-Strauss, Antonia; Pilz, Lothar R.; Strauss, Ludwig G.; Sachpekidis, Christos; Hohenberger, Peter (BioMed research international, 2013)
We used 2-deoxy-2-[18F] fluoro-D-glucose (FDG) positron emission tomography (PET) to evaluate patients with desmoid tumors undergoing therapy with imatinib. The study included 22 patients with progressive disease (PD) of a biopsy proven desmoid tumor treated orally with imatinib 800 mg daily. Patients were examined using PET prior to onset of therapy and during treatment. Restaging was performed in parallel using computed tomography (CT) and/or magnetic resonance imaging (MRI). Outcome of 22 evaluable patients was as follows: five patients with partial response (PR); twelve patients with stable disease (SD) accounting for 77% with non-progressive disease; five patients showed PD. A 30% decrease of the mean average standardized uptake value (SUV) of sequential PET examinations could be demonstrated; no patient demonstrated a substantial increase in SUV. Patients with PR/SD were matched to a group of nonprogressive disease and tested versus PD. The initial average SUV and seem to be candidates for a response prediction with an approximate -value of 0.06553 and 0.07785, respectively. This is the first larger series of desmoid patients monitored using PET showing that early SUV changes may help to discriminate responders from nonresponders and, thus, to decide whether imatinib therapy should be continued.